2007
DOI: 10.1161/01.str.0000252127.07428.9c
|View full text |Cite
|
Sign up to set email alerts
|

Serial Diffusion Tensor MRI After Transient and Permanent Cerebral Ischemia in Nonhuman Primates

Abstract: Background and Purpose-We measured the temporal evolution of the T2 and diffusion tensor imaging parameters after transient and permanent cerebral middle cerebral artery occlusion (MCAo) in macaques, and compared it to standard histological analysis at the study end point. Methods-Stroke was created in adult male macaques by occluding a middle cerebral artery branch for 3 hours (transient MCAo, nϭ4 or permanent occlusion, nϭ3). Conventional MRI and diffusion tensor imaging scans were performed 0 (acute day), 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
76
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 34 publications
(24 reference statements)
9
76
2
3
Order By: Relevance
“…3). On the other hand, a gradual increase in SIT2 has been demonstrated in ischemic lesions, 10,12,[16][17][18]20 which is consistent with the decline of DR2 observed in our Phase 2 (Fig. 4).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…3). On the other hand, a gradual increase in SIT2 has been demonstrated in ischemic lesions, 10,12,[16][17][18]20 which is consistent with the decline of DR2 observed in our Phase 2 (Fig. 4).…”
Section: Discussionsupporting
confidence: 90%
“…Human and animal studies show a decline in diŠusion anisotropy from a few hours after stroke onset, 9,[13][14][15][16][17][18] which has been attributed to vasogenic edema, membrane degradation, and cell lysis. 19 In the same time period, gradual increase in signal intensity on T2-weighted images (SIT2) has been demonstrated in ischemic lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, studies in animal models have shown correspondence between DTI measures and behavioral outcomes (8,10,62). chronic stages after ischemic injury (7,15,32,53). In order to determine whether the decrease in FA we observed in the ipsilateral IC and EC was due to demyelination or loss of axonal fibers, we next determined the axial and radial diffusivity values in each region.…”
Section: █ Discussionmentioning
confidence: 99%
“…18,[23][24][25][26] In canine stroke models, pial collateral recruitment was reported to be influenced by the following factors: vascular dynamics, systemic blood pressure and so on. 18,27 Besides, the occlusion site and the size of thrombus also had a certain impact on the infarct volume.…”
Section: Discussionmentioning
confidence: 99%